(untitled) (UNWE Yearbook, 2024)
When it comes to foreign language teaching, what is inevitable, apart from the plethora of methods, is language contact. In my opinion, awareness of language contact on the part of the teacher is without doubt necessary irrespective of learners’ level and needs. This modest paper adduces examples as a result of language contact on different linguistic levels, offers reasons as to why such examples have occurred and aims at proposing how such examples could be used by teachers to increase the effectiveness of foreign language teaching.